Konzepte des Jüdischen: Ausstellen, Aufklären, Erinnern Jüdische Museen und Vermittlungsprojekte im alemannischen Sprachraum - Pisetzki, Darja Alexandra (De Gruyter, 2022)
Museums have an important task when it comes to the subject of Judaism. Prejudices, stereotypical thinking, and sheer ignorance are widespread. What is the best way to present Jewish diversity today? The author examines how Jewish museums and education projects are facing up to this challenge and the role played by the culture of remembrance in this process, focusing on museums in Basel, Hohenems, Gailingen, and Bouxwiller.